Applicable safety analysis and biomechanical study of iliosacral triangular osteosynthesis - Jianxiong Zheng (BMC, 2021)
Abstract Background The aim of this study was to investigate the applicable safety and biomechanical stability of iliosacral triangular osteosynthesis (ITO) through 3D modeling and finite element (FE) analysis. Methods Pelvic CT imaging data from 100 cases were imported into Mimics software for the construction of 3D pelvic models. The S2-alar-iliac (S2AI) screws and S2 sacroiliac screws were placed in the S2 segment with optimal distribution and their compatibility rate on the S2 safe channel was observed and analyzed. In the FE model, the posterior pelvic ring was fixed with two transsacral screws (TTS), triangular osteosynthesis (TO) and ITO, respectively. Four different loading methods were implemented in sequence to simulate the force in standing, flexion, right bending, and left twisting, respectively. The relative displacement and change in relative displacement of the three fixing methods were recorded and analyzed. Results The theoretical compatibility rate of S2AI screw and S2 sacroiliac screw in S2 segment was 94%, of which 100% were in males and 88% in females. In the FE model, in terms of overall relative displacement, TTS group showed the smallest relative displacement, the ITO group showed the second smallest, and the TO group the largest relative displacement. The change in relative displacement of the TTS group displayed the smaller fluctuations in motion. The change in relative displacement of the TO group under right bending and left twisting displayed larger fluctuations, while the ITO group under flexion displayed larger fluctuations. Conclusions The simultaneous placement of S2AI screw and S2 sacroiliac screw in the S2 segment is theoretically safe. Although the biomechanical stability of ITO is slightly lower than TTS, it is better than TO, and can be used as a new method for the treatment of posterior pelvic ring injuries.